Augmented reality in orthopaedics: a systematic review and a window on future possibilities. (November 2019) - Laverdière, Carl; Corban, Jason; Khoury, Jason; Ge, Susan Mengxiao; Schupbach, Justin; Harvey, Edward J.; Reindl, Rudy; Martineau, Paul A.
Abstract : Aims: Computer-based applications are increasingly being used by orthopaedic surgeons in their clinical practice. With the integration of technology in surgery, augmented reality (AR) may become an important tool for surgeons in the future. By superimposing a digital image on a user's view of the physical world, this technology shows great promise in orthopaedics. The aim of this review is to investigate the current and potential uses of AR in orthopaedics. Materials and Methods: A systematic review of the PubMed, MEDLINE, and Embase databases up to January 2019 using the keywords 'orthopaedic' OR 'orthopedic AND augmented reality' was performed by two independent reviewers. Results: A total of 41 publications were included after screening. Applications were divided by subspecialty: spine (n = 15), trauma (n = 16), arthroplasty (n = 3), oncology (n = 3), and sports (n = 4). Out of these, 12 were clinical in nature. AR-based technologies have a wide variety of applications, including direct visualization of radiological images by overlaying them on the patient and intraoperative guidance using preoperative plans projected onto real anatomy, enabling hands-free real-time access to operating room resources, and promoting telemedicine and education. Conclusion: There is an increasing interest in AR among orthopaedic surgeons. Although studies show similar or better outcomes with AR compared with traditional techniques, many challenges need to be addressed before this technology is ready for widespread use. Cite this article: Bone Joint J 2019;101-B:1479–1488